Pharmacotherapy for obesity: are we ready to select, tailor and combine pharmacotherapy to achieve more ambitious goals? - Steenackers, Nele; Toumassian, Julia; Deleus, Ellen; Mertens, Ann; Lannoo, Matthias; Pazmino, Sofia; van Laar, Amar Daniël Emanuel; Van der Schueren, Bart; Vangoitsenhoven, Roman (Frontiers in Endocrinology, 2025)
Recent advancements in obesity pharmacotherapy have seen the approval of novel agents, like glucagon-like peptide-1 receptor agonist and dual agonists, offering unprecedented efficacy for obesity management. However, treatment outcomes remain highly variable, necessitating a more personalized approach to pharmacotherapy tailored to individual profiles. This review evaluates the current landscape of obesity pharmacotherapy, while exploring factors influencing variability in treatment response including early response predictors, genetic markers, and physiological traits. Additionally, the potential of combining treatment modalities and some emerging drugs are highlighted. Finally, a stepwise algorithm is proposed for personalized obesity treatment, integrating comorbidities, phenotypes, and responses to medication, paving the way for more effective and efficient obesity management.